DTC-SVM Control for Permanent Magnet Synchronous Generator based Variable Speed Wind Turbine - Youness El Mourabit; Aziz Derouich; Abdelaziz El Ghzizal; Najib El Ouanjli; Othmane Zamzoum (Institute of Advanced Engineering and Science, 2017)
In this paper, we are interested in improving the production efficiency for electric energy extracted from a wind turbine, based on a permanent magnet synchronous generator (PMSG) that we want to improve the performance by means of direct torque control with space vector modulation (DTC-SVM). The choice of this control comes from the deficiencies inherent to the conventional DTC, which includes variable switching frequency, torque ripple and implementation complexity. First we focuse on the wind energy conversion system (WECS) modeling using the PMSG machine, as well as the detailed study for the control DTC-SVM operating principle. Then, system performance is tested and compared by simulation in the MATLAB/Simulink in terms of follow instructions, robustness to the variations of the external system elements, and effectiveness of the expected method.